2016
DOI: 10.1586/17512433.2016.1172960
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of rintatolimod in the treatment of chronic fatigue syndrome/myalgic encephalomyelitis (CFS/ME)

Abstract: Chronic fatigue syndrome/ Myalgic encephalomyelitis (CFS/ME) is a poorly understood seriously debilitating disorder in which disabling fatigue is an universal symptom in combination with a variety of variable symptoms. The only drug in advanced clinical development is rintatolimod, a mismatched double stranded polymer of RNA (dsRNA). Rintatolimod is a restricted Toll-Like Receptor 3 (TLR3) agonist lacking activation of other primary cellular inducers of innate immunity (e.g.- cytosolic helicases). Rintatolimod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 86 publications
0
40
0
1
Order By: Relevance
“…3 Rintatolimod, * a specific activator of inflammatory mediator Toll-like receptor 3 (TLR3), has been used in ME/CFS treatment for decades, with varying efficacy. 11,12 With immune B cells serving as a reservoir for latent EpsteineBarr virus infection, Bcell depletion by rituximab has also been used in clinical trials and has seen some success in treating ME/CFS. 13 Combined with observations of deficient EpsteineBarr virusespecific B-cell responses in patients with ME/CFS, 14 this finding suggests that dysregulated B-cell function and persistent latent viral infection may be significant contributing factors to ME/CFS.…”
Section: Introductionmentioning
confidence: 99%
“…3 Rintatolimod, * a specific activator of inflammatory mediator Toll-like receptor 3 (TLR3), has been used in ME/CFS treatment for decades, with varying efficacy. 11,12 With immune B cells serving as a reservoir for latent EpsteineBarr virus infection, Bcell depletion by rituximab has also been used in clinical trials and has seen some success in treating ME/CFS. 13 Combined with observations of deficient EpsteineBarr virusespecific B-cell responses in patients with ME/CFS, 14 this finding suggests that dysregulated B-cell function and persistent latent viral infection may be significant contributing factors to ME/CFS.…”
Section: Introductionmentioning
confidence: 99%
“…Rintatolimod, a double-stranded RNA drug designed to increase antiviral immune response via Toll-like receptor 3 activation, is one of the only drugs to have been developed with the specific goal of treating ME/ CFS. 18,19 A 1995 study by Strayer et al 20 found significant improvements in cognitive function and memory, as well as a reduction in human herpesvirus 6 mRNA expression in 15 patients with ME/CFS who underwent long-term treatment with rintatolimod. In a second, larger-scale clinical trial in 234 patients with severe ME/CFS, results were consistent with those from the earlier trial, although improvements were somewhat reduced in magnitude.…”
Section: Antiviralsmentioning
confidence: 99%
“…In a second, larger-scale clinical trial in 234 patients with severe ME/CFS, results were consistent with those from the earlier trial, although improvements were somewhat reduced in magnitude. 21 Rintatolimod treatment has been associated with improvements in symptom burden in multiple clinical trials, 18 but has generally not been found to produce stable remission, suggesting that further studies are required.…”
Section: Antiviralsmentioning
confidence: 99%
“…Це єдиний препарат, що пройшов ІІ та ІІІ фази клінічних досліджень з підтвердженою ефективністю при внутрішньовенному застосуванні 2 рази на тиждень протягом 40 тиж у паці-Діагностика синдрому хронічної втоми Лікування синдрому хронічної втоми єнтів з тяжкою СХВ. Крім того, препарат має вищий профіль безпеки порівняно з іншими агоністами дволанцюгової РНК [33].…”
Section: інтеграція вірусного генома в клітини господаряunclassified